Evaluación del método por nutriente faltante con los elementos Nitrógeno, Potasio y Boro en el cultivo de arroz (Oryza sativa L.) - Quintana Arboleda, Héctor Jessón (2019)
VIII. SUMMARY The present experimental work was carried out in the "Sabaneta" Campus, owned by Mr. Héctor Salomón Quintana Ruiz, located on the Clementina - Montalvo highway, with the geographic coordinates of 330705.48 UTM South Latitude, 197465.35 West Longitude, with a height of 8 msmn The area has a tropical climate, with an average annual temperature of 25.6 ° C, annual precipitation 1 730 mm, relative humidity of 82%. The soil is of alluvial origin, flat topography, clay loam texture, drainage and regular fertility. The rice seed variety Iniap FL 1480 "Cristalino" was used. The treatments that were used were constituted by fertilizers with the respective doses, such as Nitrogen + Potassium + Boron (dose of 133.2 + 157.2 + 0.096 kg / ha); Nitrogen + Potassium (dose of 133.2 + 157.2 kg / ha); Nitrogen + Boron (dose of 133.2 + 0.096 kg / ha); Potassium + Boron (dose of 157.2 + 0.096 kg / ha); Nitrogen (dose of 133.2 kg / ha); Potassium (dose of 157.2 kg / ha); Boron (dose of 0.096 kg / ha) and an absolute Control without application of fertilizers. The experimental design "Complete blocks at random" was used, with eight treatments and three repetitions. The statistical difference between the means of the treatments was determined with the Tukey test at 95% probability. All the tasks required for rice cultivation for normal development, such as land preparation, sowing, fertilization, irrigation, weed control, insect control, pests and diseases, and harvesting, were carried out. Based on the results obtained, it was determined that the rice culture obtained a differentiated response due to the influence of the missing nutrients of Nitrogen, Potassium and Boron; the highest plant height, tillers and panicles / m2 and panicle length was presented with the use of nitrogen + potassium in a dose of 133.2 + 157.2 kg / ha; The grain-straw ratio, percentage of full and void grains did not report significant differences in their averages and the highest yield of the crop was reported with the use of nitrogen + potassium in a dose of 133.2 + 157.2 kg / ha, as well as the highest net profit $ 242.20.